Comparison of surgical and pathological parameters after laparoscopic transperitoneal pelvic/para-aortic lymphadenectomies. Issue 11 (November 2020) - Jacob, Anna; Plaikner, Andrea; Schneider, Achim; Favero, Giovanni; Tozzi, Roberto; Mallmann, Peter; Domröse, Christian; Martus, Peter; Marnitz, Simone; Barinoff, Jana; Kohler, Christhardt
Abstract : Objective: Lymphadenectomy is an integral part of surgical staging and treatment for patients with gynecologic malignancies. Since its introduction, laparoscopic lymphadenectomy has proved feasible, safe, and oncologically adequate compared with open surgery while morbidity is lower and hospital stay considerably shorter. The aim of this study was to examine if surgical outcomes may be improved after the initial learning curve is complete. Methods: An analysis of 2535 laparoscopic pelvic and/or para-aortic lymphadenectomies was performed between July 1994 and March 2018 by one team of gynecologic oncology surgeons but with the consistent supervision of a consultant surgeon. Data were collected prospectively evaluating operative time, intra-operative and post-operative complications, number of lymph nodes, and body mass index (BMI). Previously published data of 650 patients treated after introduction of the method (period 1, 1994–2003) were compared with the latter 524 patients (period 2, 2014–2018). Results: The median age of the 2535 patients was 43 years (IQR 34–57). The most common indication for pelvic and/or para-aortic lymphadenectomy was cervical cancer (n=1893). Operative time for para-aortic lymph node dissection was shorter in period 2 (68 vs 100 min, p<0.001). The number of harvested lymph nodes was increased for pelvic (19.2 (range 2–52) vs 21.9 (range 4–87)) and para-aortic lymphadenectomy (10.8 (range 1–52) vs 14.4 (range 4–64)), p<0.001. BMI did not have a significant influence on node count or operative time, with BMI ranging from 14.6 to 54.1 kg/m 2 . In contrast to period 1 (n=18, 2.9%), there were no intra-operative complications in period 2 (n=0, 0.0%, p<0.001) whereas post-operative complications were similar (n=35 (5.8%) in period 1; n=38 (7.6%) in period 2; p=0.32). Conclusion: In this large cohort of patients who underwent laparoscopic transperitoneal lymphadenectomy, lymph node count and peri-operative complications improved after the initial learning curve.